Arsenic and heavy metal contamination in drinking water from an industrial zone in Dhaka District, Bangladesh - Md Kamal Hossain; Salma Sultana; Afroza Parvin; Fahima Islam; Mohammad Moniruzzaman; Badhan Saha; Afsana Parvin; H. M. Solayman; Sumaia Sharmin (PLoS ONE, 2025)
Heavy metals (HMs), even in trace concentrations, can pose serious health risks when consumed over time. In Bangladesh, the widespread use of tube wells for drinking water, coupled with industrial activity, has contributed to the contamination of groundwater with HMs. This study investigated heavy metal contamination in drinking water samples from Gazipur, an industrial hub, using Inductively Coupled Plasma-mass Spectrometry (ICP-MS). The results revealed that the mean concentrations of HMs in mg/L followed the order: Fe (5.479 ± 3.740)> Mn (0.203 ± 0.233)> Pb (0.133 ± 0.370)> Zn (0.068 ± 0.070)> Cu (0.016 ± 0.034)> As (0.003 ± 0.004)> Ni (0.002 ± 0.001)> Cr (0.002 ± 0.001). Concentrations of Pb, Fe, and Mn exceeded safe limits while As, Cd, Cr, Ni, Cu, and Zn were within acceptable ranges. The scatter plot analysis revealed weak and non-significant correlations between As concentrations and other heavy metals with low R² values. A strong difference in metal contamination levels between shallow (20–80 meters) and deep wells (>80 meters), with shallow wells exhibiting significantly higher contamination percentages, often approaching 100%, while deep wells consistently remained below 30%. Ecological risk assessments showed low to moderate contamination at most sampling sites. Health risk evaluations (HQ and HI) indicated that all metals remained below harmful levels, though arsenic posed a heightened cancer risk, particularly for children. Principal Component Analysis (PCA) and Cluster Analysis suggested that As, Pb, Fe, Zn, and Mn were linked to industrial activities, while the other metals were likely of geological origin. The study emphasized the need for ongoing surveillance and intervention to protect public health in areas impacted by industrial pollution.